Pediatric student’s case history and peculiarities of Pediatric Physical Examination - Kyzyma, N. V.; Ivanko, O. G.; Krut, A. S.; Radutnaya, E. A.; Pidkova, V. Y.; Pashenko, I. V.; Nedelskaya, E. V.; Кизима, Наталя Володимирівна; Іванько, Олег Григорович; Круть, Олександра Степанівна; Радутна, Олена Анатоліївна; Підкова, Віра Ярославівна; et al. (Zaporiz'kyj derzhavnyj medychnyj universytet, 2013)
The handbook can be used by teachers and students at practical classes and for module control in supervision of patients, as well as for independent work in case of filling in a case history of the patient in the discipline “Propedeutic pediatric”. The textbook contains tables, charts and glossary of medical terms which is required for patient interviewing. The content of the textbook corresponds to the requirements of “Educational qualification characteristics of the specialist in specialty 7.120101 “General Medicine”.